Patterns of Hearing Loss Following Retrosigmoid Excision of Unilateral Vestibular Schwannoma - Babbage, Melissa J.; Feldman, Melanie B.; O'Beirne, Greg A.; MacFarlane, Martin R.; Bird, Philip A. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives To determine the pattern of auditory responses, time-course of hearing deterioration, and possible site of lesion following retrosigmoid excision of unilateral vestibular schwannomas.Design Prospective, nonrandomized, observational pilot study.Setting Tertiary referral medical center.Main outcome measures Preoperative and postoperative pure-tone and speech audiometry, auditory brainstem response testing, and distortion product otoacoustic emissions were performed in 20 patients. Testing was conducted every 24 hours for the duration of hospitalization. Transtympanic electrocochleography was performed if delayed deterioration of auditory responses was documented.Results Of the 20 patients, 7 had no discernible cochlear nerve at the end of the procedure. Of the 13 patients with an intact nerve, 6 retained hearing, 3 with evidence of reduced neural function. Of the 7 who lost hearing despite an intact nerve, 5 lost at least cochlear and possibly also neural function, and 1 had reduced neural function but retained cochlear function. There were two examples of delayed deterioration of cochlear nerve responses.Conclusions Hearing loss following retrosigmoid removal of vestibular schwannomas most often involves loss of at least cochlear function, possibly in addition to neural damage. In a smaller number of cases anacusis or hearing deterioration can be attributed to purely neural trauma.
Keywords: acoustic neuroma; vestibular schwannoma; hearing preservation